2022
DOI: 10.1002/mgg3.2049
|View full text |Cite
|
Sign up to set email alerts
|

Spinal muscular atrophy carrier frequency in Saudi Arabia

Abstract: Background: Spinal Muscular Dystrophy (SMA) is one of the leading causes of death in infants and young children from heritable diseases. Although no largescale popultion-based studies have been done in Saudi Arabia, it is reported that the incidence of SMA is higher in the Saudi population partly because of the high degree of consanguineous marriages. Methods:The final analysis included 4198 normal volunteers aged between 18 and 25 years old, 54.7% males, and 45.3% females. Whole blood was spotted directly fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…As of the current, SMA carriers screening is already open worldwide ( 14 , 27 29 ), and even has been conducted in most areas of China ( 16 , 17 , 19 , 30 34 ). In this study, we identified 726 SMA carriers from 39,647 participants who were screened for SMA in Lanzhou City, Gansu province.…”
Section: Discussionmentioning
confidence: 99%
“…As of the current, SMA carriers screening is already open worldwide ( 14 , 27 29 ), and even has been conducted in most areas of China ( 16 , 17 , 19 , 30 34 ). In this study, we identified 726 SMA carriers from 39,647 participants who were screened for SMA in Lanzhou City, Gansu province.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Morocco reported a carrier frequency of 1 in 25 and a prevalence of 1:1900, though this was based on a small sample of 150 Moroccan newborns 16 . While this work was in preparation, a study was published whereby screening 4,189 normal Saudi volunteers determined a carrier frequency of 1 in 38 17 . Using this SMA allele frequency, and the coe cient of inbreeding in Saudi Arabia 18 , we estimated SMA incidence in this country to be 1 in 3,192 (Table 1), which is consistent with that estimated by authors in this study (32 in 100,000 or 1 in 3,125 births) 17 .…”
Section: Sma Epidemiology Other Arab Populationsmentioning
confidence: 99%
“…Estimates of SMA births in UAE and KSA and the associated cost of postnatal treatment versus premarital screening Calculated by multiplying incidence in Table1by annual births in each country; # $2.1 million dollar; ^Calculated by multiplying cost of SMA testing ($50) per couple; $ calculated by multiplying the number of couples expected to have an SMA birth and requiring PGT/IVF (pre-implementation genetic testing/in vitro fertilization) by cost of PGT/IVF (30,000 USD 20 ); & calculated by subtracting cost of premarital screening and PGT/IVF from total cost of gene therapy We estimate the disease burden or incidence of SMA in the UAE. Using data from the UAE (this study) and Saudi Arabia17 , we demonstrate that, in addition to potentially preventing new SMA cases, premarital screening and subsequent PGT/IVF for at-risk couples, can be a highly cost-effective measure from a public health standpoint, leading to an expected 16 to 28-fold cost reduction compared to postnatal disease treatment. Interestingly, the cost savings due to premarital screening for this one disease (~$10 million in UAE and $324 million in KSA) is su cient to fund more comprehensive premarital genomic screening programs encompassing hundreds of recessive disorders in both countries.…”
mentioning
confidence: 91%
“…However, estimates suggest that it ranges from 1 to 2 per 100,000 individuals, with an incidence of 8–10 per 100,000 live births ( 15 ). Higher prevalence rates have been observed in Middle Eastern countries such as Saudi Arabia, where recent studies estimated roughly 2,265 SMA patients, possibly due to prevalent consanguineous marriages ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Canadian research involving over 900 patients and caregivers highlighted significant costs to families of SMA patients, with median health expenditures for assistive devices, healthcare professional services, and accommodation and travel, along with a notable negative impact on patient quality of life ( 20 ). Although SMA is a rare health condition, its incidence rate is believed to be increasing in the kingdom mainly due to high rate of consanguinity and allocating more financial resources for preventative (e.g., premarital screening) and early detection and treatment measures (e.g., newborn screening, early initiation of therapy) is necessary ( 16 ).…”
Section: Introductionmentioning
confidence: 99%